Pro Tools 101 : official courseware, version 8.0. - Digidesign, ....-; Cook, Frank D., ....- (Boston : Course Technology, 2008)
Previously available only through Digidesign® training partner schools, Digidesign's Pro Tools 101 Official Courseware - the textbook for the first course of the Digidesign Training and Education Program - is now available directly through the online DigiStore, major book and music retailers, and Digidesign training partner schools. This is the first Pro Tools educational book authored by Digidesign that is available through other sources in addition to Digidesign training partner schools. Use it to study Pro Tools® basics on your own or as a first step toward formal Pro Tools Certification through a Digidesign training partner school. This book is the only stand-alone offering that is part of the path to Pro Tools Operator Certification. Build Your Pro Tools Foundation The Pro Tools 101 Official Courseware takes a comprehensive approach to learning the fundamentals of Pro Tools|HD®, Pro Tools LE, or Pro Tools M-Powered systems. Learn to build sessions that include multi-track recordings of live instruments, MIDI sequences, software synthesizers and samplers, and audio looping with REX or ACID files. Through hands-on tutorials, develop essential techniques for recording, editing, and mixing. The included DVD-ROM offers tutorial files and videos, plug-in installers, and a variety of Pro Tools sessions. Now updated for Pro Tools 7 software, this new edition from the definitive authority on Pro Tools covers everything you need to know to complete a Pro Tools project.
Updated for Pro Tools 8
Keywords: Computers -- Muziek; Muziek -- Programmeren; Pc-Tools.